Burden and Distress in Caregivers of Patients With Panic Disorder and Agoraphobia - Borgo, Evandro Luis Pampani [UNESP]; Abreu Ramos-Cerqueira, Ana Teresa de [UNESP]; Torres, Albina Rodrigues [UNESP] (Lippincott Williams & Wilkins, 2017)
We estimated the prevalence, severity, and correlates of burden and distress in caregivers of patients with panic disorder and agoraphobia. The instruments used in this cross-sectional study with 40 caregivers and 40 outpatients were Carer Burden Interview (CBI), Family Burden Interview Schedule (FBIS-BR), Self-Reporting Questionnaire (SRQ), Panic and Agoraphobia Scale (PAS), and Mini-international Neuropsychiatric Interview. Bivariate analyses were followed by regression analyses. The patients' mean PAS score was 29.6, and the mean scores in the caregivers' burden scales were 27 (CBI) and 1.64 (FBIS-BR). Distress (or common mental disorder [CMD]) occurred in 37.5% and was associated with higher burden. In the multivariate analysis, the SRQ score was predicted by female sex and worse self-evaluation of health, the CBI score by CMD and public service, the FBIS-BR score by CMD and not living with the patient, the FBIS-objective score by CMD and being employed, the FBIS-subjective score by CMD, and the level of worry by the severity of patients' avoidance and panic attacks.
Keywords: Panic disorder; agoraphobia; caregivers; burden; distress; common mental disorder